Geologi Situs Bawömataluö, Kecamatan Fanayama, Kabupaten Nias Selatan, Provinsi Sumatera Utara - Lucas Partanda Koestoro; Muhammad Fadlan S Intan (Balai Arkeologi Sumatera Utara, 2016)
AbstractThe Megalithic tradition of Nias is a living Megalithic tradition as a result of the cultural development that has been going on since the prehistoric period. The Megalithic tradition was introduced during a period between the Neolithic and Palaeometalic. Research on Nias Island was carried out at Bawömataluö Site, which is administratively located at Bawömataluö Village, Fanayama District, South Nias Regency, North Sumatra Province. The problems discussed here are the morphological unit that formed the site, stratigraphical sequence, geological structure, and the source of raw material to make Megalithic objects. The aim of the research is to understand the geological condition of the natural environment of Bawömataluö Site and its surroundings. Geological survey, petrology analyses, and interpretation of geological map are the methods used. The results show that Bawömataluö Site is situated on the slightly wavy morphological unit, which was shaped by Lelematua Formation. Observation on the geological structure reveals that Bawömataluö Site stands on the uplifted part (block-hanging wall) of a thrust fault. Regarding the source of raw material to make Megalithic objects, observation reveals that the stones were taken from Batubuaya River, which is 1.5 kilometers to the southwest of Bawömataluö.AbstrakTradisi megalitik Nias merupakan tradisi megalitik berlanjut sebagai hasil pertumbuhan dan perkembangan budaya yang terjadi sejak masa prasejarah, yang berkembang di Nusantara antara masa neolitik dan paleometalik. Penelitian di Pulau Nias dilaksanakan di Situs Bawömataluö di wilayah administratif Desa Bawömataluö, Kecamatan Fanayama, Kabupaten Nias Selatan, Provinsi Sumatera Utara. Permasalahan yang dibahas adalah berapa satuan morfologi yang menyusun situs, urutan stratigafi, struktur geologi, dan lokasi sumber bahan batuan. Tujuan penelitian adalah untuk mengetahui kondisi lingkungan geologi Situs Bawömataluö dan sekitarnya. Metode yang digunakan adalah survei geologi, analisis petrologi, dan interpretasi peta. Hasil yang diperoleh bahwa Situs Bawömataluö terletak pada satuan morfologi bergelombang lemah, yang tersusun oleh Formasi Lelematua. Aspek struktur geologi menghasilkan data bahwa Situs Bawömataluö terletak pada bagian yang naik (blok hanging wall) dari suatu sesar naik (thrust fault). Adapun lokasi pengambilan bahan batuan untuk pembuatan bangunan megalitik berada pada Sungai Batubuaya yang berjarak 1,5 km di arah baratdaya SitusBawömataluöa.